2017
DOI: 10.1139/cgj-2016-0281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grass roots on soil-water retention curve and permeability function

Abstract: The effects of Vetiver grass (Chrysopogon zizanioides) roots on the soil-water retention curves (SWRCs), permeability (k) function, and saturated permeability, ksat, have been investigated on clayey sand (SC) and low-plasticity silt (ML). For ML soil, when the root biomass per soil volume was lower than 6.5 kg/m3, the saturated permeability increased, the air-entry suction decreased slightly, and the SWRC became steeper with increasing root contents, probably due to the formation of cracks caused by wetting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 50 publications
2
44
0
2
Order By: Relevance
“…Studies that focus on relatively young plants found slowing of infiltration (Gish & Jury, 1983;Leung et al, 2015;Jotisankasa & Sirirattanachat, 2017) presumably due to root occupancy of soil pore space, which blocks water flow paths (Scholl et al, 2014;Ng et al, 2016). In contrast, increased infiltration rate is more often reported in mature plants (van Noordwijk et al, 1991;Mitchell et al, 1995;Ng et al, 2017), and is attributable to the formation of (a) root channel related macropores associated with root decay (Ghestem et al, 2011) or (b) desiccation cracks upon drying of medium-to high-plasticity clay (Zhan et al, 2007;Jotisankasa & Sirirattanachat, 2017;Song et al, 2017). The existing research often considered plant effects only at one particular plant age.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that focus on relatively young plants found slowing of infiltration (Gish & Jury, 1983;Leung et al, 2015;Jotisankasa & Sirirattanachat, 2017) presumably due to root occupancy of soil pore space, which blocks water flow paths (Scholl et al, 2014;Ng et al, 2016). In contrast, increased infiltration rate is more often reported in mature plants (van Noordwijk et al, 1991;Mitchell et al, 1995;Ng et al, 2017), and is attributable to the formation of (a) root channel related macropores associated with root decay (Ghestem et al, 2011) or (b) desiccation cracks upon drying of medium-to high-plasticity clay (Zhan et al, 2007;Jotisankasa & Sirirattanachat, 2017;Song et al, 2017). The existing research often considered plant effects only at one particular plant age.…”
Section: Introductionmentioning
confidence: 99%
“…Jotisankasa and Sirirattanachat (2017) shows that root effects on hydraulic conductivity were prominent only when matric suction was less than 10 kPa, whereas the hydraulic conductivity measured by Song et al (2017) found that roots affect unsaturated hydraulic conductivity for the entire suction range considered (< 100 kPa). Thus, the presence of plant roots does not necessarily always reduce or increase unsaturated hydraulic conductivity, depending both on the plant and soil types.…”
Section: Introductionmentioning
confidence: 88%
“…Some studies (Table 1) showed an increase in water retention capability when plant roots are present in the soil (Scanlan & Hinz, 2010;Rahardjo et al, 2014;Leung et al, 2015;Ng et al, 2016a, b;Jotisankasa & Siririrattanachat, 2017), probably because of the blockage of soil pore space by roots (Buczko et al, 2007). However, some studies reported an opposite result Jotisankasa and Sirirattanachat, 2017), arguably because of the formation of soil cracks due to, for instances, repeated soil shrinkage, swelling and root decay and growth (Vergani & Graf, 2015;Ng et al, 2016a;Ni et al, 2017;Leung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can provide additional slope stabilization effect further through transpiration, whereby soil moisture is extracted from the ground, thus increasing the soil suction and shear strength [15][16]. The roots can also affect soil's hydraulic conductivities, soil-water retention, and infiltration capacity in several opposing ways depending on root contents and growing stage [15,17]. Active growing roots tend to decrease permeability while decaying roots can increase macrovoid content, soil permeability, and infiltration into the soil.…”
Section: Introductionmentioning
confidence: 99%